Efficiency of pepper farms in Sarawak - Rosli, Anita (2013)
Pepper is one of the important crops and source of income for 67,000 families in the interior areas of Sarawak. However, pepper farmers faced a few major problems such as the increasing cost of inputs, escalating management cost of pest and disease attacks, and fluctuating pepper price at international market (DOA, 2012). Pepper farming requires a proper management of resources and farming operations to ascertain high yield at minimum cost and increase farm profit. The previous studies about efficiency in pepper production in Sarawak by Noorzakiah, Alias, and Sazali (1993), Mohd, Alias, and Ruhana (1993), and Hamid and Mansor (1997) found that pepper farms in Sarawak were inefficiently in resource use. However, there are various factors influence relative performance and efficiency level among pepper farms such as market factors, geographical location, socioeconomic background, farming practices, and government intervention. Thus, a single decision can easily make a difference between efficiency and inefficiency of pepper farms. Therefore, this study is carried out to analyze the performance of pepper farms in Sarawak by estimating the level of efficiency of pepper farms. A sample of 678 pepper farmers was selected for this study through field survey that was conducted from August to December 2009. Stochastic Frontier Analysis (SFA) and Data Development Analysis (DEA) method were applied to estimate technical, allocative, economic, and cost efficiency of pepper farms. The inefficiency model and Tobit model were used to investigate the determinants of efficiency in pepper farming. The factors of the adoption of farming technology in pepper farming among farms are estimated using Logit model. The mean technical efficiency, allocative efficiency, and economic efficiency were estimated to be 0.518, 0.496, and 0.258 respectively by using SFA method. From DEA model, the mean technical efficiency under constant returns to scale (CRS) and variable returns to scale (VRS) were 0.567 and 0.661 respectively while the mean allocative efficiency and cost efficiency were estimated to be 0.585 and 0.438 respectively. The mean efficiency scores from DEA model were higher than SFA model, these results indicate that DEA model fitted tightly to the data set compared than SFA. Pepper farms are inefficient since the mean of technical, allocative, economic, and cost efficiency of pepper farms are low. Farmers are technically inefficient in input utilization and inefficient in input allocation hence they are not maximizing the output and not minimizing cost. The inefficiencies among pepper farms are due to improper farm management and misallocation of inputs. Besides, inefficiencies among farms also due to the age of farmers where majority of sample farmers are consist of older farmers. However, the efficiency in farm management is positively and significantly influenced by education level, the frequency of contacts with extension agents per year, being member of farmer’s organization, being full-time pepper farmers, and attending farming courses and study visits. Therefore, it is imperative that farmers should improve their farm performance and efficiency level through effective of agronomic education and extension services.